Rasa nyeri pada mukosa jaringan pendukung gigitiruan penuh dan penanggulangannya Pain on supported tissue mucosa of full denture and its relief - Taufik Sumarsongko; Aprillia Adenan (DiscoverSys Inc., 2011)
Dentures painful and uncomfortable at alveolar ridge denture support of oral mucosa is the most common symptomof denture wearers. The aim of this article is to provide guidelines for optimal using of the media and to identifyalternative uses that could be considered in daily practice. Soreness of oral mucosa under a denture, like all pain iscomplex uncomfort experience, in which multitude of factors interact from the emotional to the physical. Unevenpressure on tissue support under a denture base is probably initially caused irritate to denture bearing tissue,contribute to causing inflamation and increased sensitivity. It should be possible to identify which of the majoretiological agent is causing the pain and rapidly treatment.